Biodegradable poly-lactic acid based-composite reinforced unidirectionally with high-strength magnesium alloy wires. (May 2015) - Li, X.; Chu, C.L.; Liu, L.; Liu, X.K.; Bai, J.; Guo, C.; Xue, F.; Lin, P.H.; Chu, Paul K.
Abstract: Biodegradable poly-lactic acid (PLA) – based composites reinforced unidirectionally with high-strength magnesium alloy wires (MAWs) are fabricated by a heat-compressing process and the mechanical properties and degradation behavior are studied experimentally and theoretically. The composites possess improved strengthening and toughening properties. The bending strength and impact strength of the composites with 40 vol% MAWs are 190 MPa and 150 kJ/m 2, respectively, although PLA has a low viscosity and an average molecular weight of 60, 000 g/mol. The mechanical properties of the composites can be further improved by internal structure modification and interface strengthening and a numerical model incorporating the equivalent section method (ESM) is proposed for the bending strength. Micro arc oxidization (MAO) of the MAWs is an effective interfacial strengthening method. The composites exhibit high strength retention during degradation and the PLA in the composite shows a smaller degradation rate than pure PLA. The novel biodegradable composites have large potential in bone fracture fixation under load-bearing conditions.